"It was the worst time in my life": The effects of emotionally abusive coaching on female Canadian national team athlete - Kerr, G.; Willson, E.; Stirling, A. (Women in Sport and Physical Activity Journal, 2020)
This study sought to explore the long-term effects of emotionally abusive coaching on female athletes. Although the long-term effects of childhood emotional abuse are well-documented in the child abuse literature, this question has not been explored empirically in the domain of sport, an environment in which emotionally abusive coaching practices are known to be common. In various prevalence studies of athlete maltreatment in sport internationally, emotional abuse is the most frequently experienced form and yet the long-term implications of these experiences are not well-understood. This study involved interviews of eight retired, elite, female Canadian National Team members. The findings revealed that athletes reportedly experienced different effects depending on whether they were in their competitive careers, in the retirement transition, or in post-transition life. All of the athletes required professional psychological assistance to help them recover from their emotionally abusive experiences; for some, this process continued for six years post-retirement. The effects described by the athletes resembled the symptoms associated with Post-Traumatic Stress Disorder suggesting an important line of future research. Until coaching practices become abuse-free, these findings also indicate a clear need for the provision of psychological supports and resources for athletes during and post-athletic career.